Can preoperative computed tomography predict tissue origin of primary maxillary cancer?. Issue 40 (October 2016) - Yuan, Ying; Wang, Jingbo; Wu, Yingwei; Li, Guojun; Tao, Xiaofeng
Abstract : Abstract: Based on the histopathologic origin, malignant maxillary neoplasms may share some clinical characteristics but have different biological behavior, treatments, and prognoses. The aim of the present study was to explore the association between CT characteristics and tissue origin of primary maxillary cancer (MC). A retrospective review of CT findings was performed in patients diagnosed with MC between January 1, 2005 and December 31, 2013. Univariate and multivariable logistic regression analyses were performed to determine the association between tissue of origin and CT characteristics, with adjustment for possible confounding factors. A total of 164 patients (70 male, 94 female, age: 46.8 ± 18.3 years) were included. Patients were divided into epithelial (n = 88) and nonepithelial (n = 76), or odontogenic (n = 15) and nonodontogenic (n = 149) groups. After adjusting for age, sex, smoking status, alcohol use, tumor size, and stage in the multivariable logistic regression model, the lesions with cortical bowing were found more likely to be epithelial (odds ratio [OR] = 7.0, 95% confidence interval [CI], 1.4–36.1) than nonepithelial origin, while lesions with cervical lymphadenopathy were more associated with a nonodontogenic origin (OR = 12.6, 95% CI, 1.1–140.0) rather than odontogenic. Among epithelial cancers, lesions with cortical bowing were 14 times more likely to be salivary gland-type (OR = 13.8, 95% CI, 1.3–141.5). CT characteristics of cortical bowing and cervical lymphadenopathy might be suggestive of tissue origin in MC. Larger prospective studies are warranted to further examine the association.